The use of Data in Assessing and Designing Insolvency Systems - Garrido, José (IMF working paper ;, 2019)
To date, the use of empirical data in insolvency law analysis has been sporadic. This paper provides a conceptual framework for the use of data to assess the effectiveness and efficiency of insolvency systems. The paper analyzes the existing sources of data on insolvency proceedings, including general insolvency statistics, judicial statistics, statistics of insolvency regulators and other sources, and advocates for the design of special data collection mechanisms and statistics to conduct detailed assessments of insolvency systems and to assist in the design of legal reforms.